Allele, genotype, and composite genotype effects of IL-1A +4845 and IL-1B +3954 polymorphisms for chronic periodontitis in an Indian population - R Gayathri; Abdul Vahab Saadi; K Mahalinga Bhat; Subraya G Bhat; Kapaettu Satyamoorthy (Wolters Kluwer Medknow Publications, 2011)
Introduction: The pro-inflammatory cytokine interleukin-1 (IL-1) is a key modulator of host responses to microbial infection and a major modulator of extracellular matrix catabolism and bone resorption, and polymorphisms in the IL-1 gene cluster have been associated with an increased risk of developing severe adult periodontitis. A case control study was performed to determine the role of IL-1A+4845 and IL-1B+3954 polymorphisms in the predisposition to chronic periodontitis. Materials and Methods: The study was conducted with 103 unrelated participants recruited from Manipal College of Dental Sciences, Manipal, which included 51 chronic periodontitis patients and 52 normal periodontally healthy individuals. Extensive clinical data were collected, bone loss was the major outcome variable and smokers and diabetics were excluded from the study to eliminate the influence of these risk factors. Genomic DNA was isolated from the blood samples of participants for genotyping IL-1A+4845 and IL-1B+3954 polymorphisms by polymerase chain reaction-restriction fragment length polymorphism and the data statistically analyzed. Results: Allele 2 of the IL-1A+4845 polymorphism was carried by 38% of all participants; of these only 6 were homozygous for the allele. Allele 2 of the IL-1B+3954 was carried by 21% of the subjects; only 1 was homozygous for allele 2. The composite genotype was carried by 31% of the cases and by 38% of the controls. Overall, 35% participants carried the composite IL-1 genotype. No statistically significant association was found for the distributions. Conclusions: The distribution of the IL-1 positive composite genotype is in concordance with the frequencies reported in the Caucasians. Association was not found for the effect of allele, genotype, composite genotype, and haplotypes of IL-1A+4845 and IL-1B+3954 polymorphisms with periodontitis. Its utility as a risk marker in this population was not borne out by the study.